Pathophysiological Role of Proteasome-Dependent Proteolytic Pathway in Endothelin-1-Related Cardiovascular Diseases - Takaoka, M.; Ohkita, M.; Matsumura, Y. (Current Vascular Pharmacology, 2003)
A proteasome-dependent proteolytic pathway serves important functions in cell cycle control and transcriptional regulation; however, its pathophysiological role in cardiovascular diseases is still unclear. We have recently obtained evidence that proteasome inhibitors are capable of preventing the development of deoxycorticosterone acetate (DOCA)-salt-induced hypertension or hypertrophy and of ischemic acute renal failure (ARF). Beneficial effects of the proteasome inhibitors were accompanied by a decrease in endothelin-1 (ET-1) content in the aorta and kidney of DOCA-salt and ischemic ARF animals, respectively. In addition, there is evidence showing that the reduction of nuclear factor-kB (NF-kB) activation is involved in the mechanisms for suppressive effects of proteasome inhibitors on ET-1 gene transcription and the consequent decrease in ET-1 mRNA expression in the cultured vascular endothelial cells. These findings suggest that a proteasome-dependent proteolytic pathway has a crucial role in the pathogenesis of ET-1-related cardiovascular diseases, probably through the activation of NF-kB, and also that the use of proteasome inhibitors may be a novel approach to the treatment of cardiovascular diseases.
Keywords: proteasome